Les Francophones et les études postsecondaires - Tardif, Claudette; McMahon, Frank (Canadian Journal of Higher Education, 1989)
Francophones intending to pursue post-secondary studies in French face two major problems. The article examines the current status of post-secondary education provided to the francophone minority outside Québec. It first notes the problem of accessibility of French-language post-secondary institutions and the phenomenon of francophone assimilation, and then goes on to study the effects on Francophones of bilingual post-secondary institutions. The authors summarize the relevant research and statistics and share the results of their various experiences in establishing exclusively French-language schools in Alberta.